Utilization of Macromedia Flash in Mathematics Learning - Ikram Lihu; Nirsal Nirsal; Syafriadi Syafriadi (Jurnal Literasi Digital, 2023)
This research is to find out whether there is an increase in mathematics learning outcomes in flat shape material after being taught using learning media using macromedia flash and how to find out the effectiveness of learning using learning media using macromedia flash. This research was carried out at the Palopo Model State MTs for the 2021/2022 Academic Year. This research uses The One Group Pretest-Posttes Design. The experimental units in this study were determined randomly from all class VII. The data collection technique in this study was to use tests, namely pretest and posttest, student activity observation sheets and student response questionnaires. The results of students' mathematics learning before being taught using learning media by utilizing macromedia flash on flat shape materials have an average value of 50.50. The results of students' mathematics learning after being taught using learning media by utilizing macromedia flash on flat shape material have an average value of 72.65. Student activity when learning media was applied using macromedia flash on flat shape material was active, namely 2.68. Student response when learning media was applied using macromedia flash on flat shape material was in the good category, namely 3.1. There is an increase in mathematics learning outcomes in students' flat shape material after being taught using learning media using macromedia flash with an average acquisition of 72.65. The results of inferential statistical analysis using the t-test concluded that learning media using macromedia flash on student data structure material is said to be effective because it meets the criteria for learning effectiveness. The novelty in this study can be seen in the average achievement of each good aspect of learning media using Macromedia Flash which is in the active category, as well as the responses of students who are taught with learning media using Macromedia Flash which are in the good category.